The Influence of Digital Payments, Financial Literacy, and Financial Management on the Performance of MSMEs in Tenggilis Mejoyo District, Surabaya - Alma Cynthia; Muslimin Muslimin (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to identify the factors influencing the performance of MSMEs in Tenggilis Mejoyo District, Surabaya. Digital payment, financial literacy, and financial management serve as the independent variables in this research. A quantitative approach is employed, focusing on MSMEs located in Tenggilis Mejoyo District, Surabaya. The incidental sampling method was used to collect a sample of 94 respondents. Smart-PLS 4.0 was utilized to analyze SEM-PLS data. The results indicate that digital payment has no significant effect on MSME performance. Meanwhile, financial literacy and financial management significantly influence MSME performance.